2005
DOI: 10.1074/jbc.m410844200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transcriptional Networks during Liver Regeneration

Abstract: The molecular analysis of mammalian cellular proliferation in vivo is limited in most organ systems by the low turnover and/or the asynchronous nature of cell cycle progression. A notable exception is the partial hepatectomy model, in which quiescent hepatocytes reenter the cell cycle and progress in a synchronous fashion. Here we have exploited this model to identify regulatory networks operative in the mammalian cell cycle. We performed microarray-based expression profiling on livers 0 -40 h post-hepatectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
92
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 54 publications
18
92
1
3
Order By: Relevance
“…Ccne expression peaks at 24 h in zebrafish regenerating livers and at 40 h in mice. Transcription of TOP2A is directly regulated by UHRF1 (23,28), and Top2a is up-regulated during mouse liver regeneration (38) with the same kinetics that we observe for Uhrf1. To determine whether heterozygous mutation of uhrf1 hinders its capacity to activate top2a during liver regeneration, we used Q-PCR to compare its expression in livers from uhrf1 ϩ/ϩ and uhrf1 ϩ/Ϫ zebrafish at the peak time of uhrf1 expression after PH (36 h).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Ccne expression peaks at 24 h in zebrafish regenerating livers and at 40 h in mice. Transcription of TOP2A is directly regulated by UHRF1 (23,28), and Top2a is up-regulated during mouse liver regeneration (38) with the same kinetics that we observe for Uhrf1. To determine whether heterozygous mutation of uhrf1 hinders its capacity to activate top2a during liver regeneration, we used Q-PCR to compare its expression in livers from uhrf1 ϩ/ϩ and uhrf1 ϩ/Ϫ zebrafish at the peak time of uhrf1 expression after PH (36 h).…”
Section: Resultssupporting
confidence: 59%
“…UHRF1 directly activates TOP2A transcription in vitro (25,27,28), and Top2a up-regulation after PH has been reported in mice (38,44) and, shown here, in zebrafish. Interestingly, top2a expression after PH in zebrafish requires uhrf1, providing an in vivo example of this relationship and suggests a mechanism by which uhrf1 mutation hampers liver regeneration.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, it has been reported that the overexpression of the mouse ortholog of REG1A under the rat glucagon promoter led to the development of rare tumors, including HCCs, in transgenic mice consistent with tumor-promoting activity (Yamaoka et al, 2000). Furthermore, REG1A and REG3A have recently been found overexpressed during rodent liver regeneration after hepatectomy (White et al, 2005). The REG proteins are associated with inflammation and regenerative processes and therefore we searched for an association between REG expression and clinicopathological features, chronic viral infection or alcohol abuse, but no statistically significant correlation was found.…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as Igfbp1, LCN2, and Saa2 are upregulated, whereas Car3, Serpina6, and Cyp2f2 are down-regulated ( Fig. 1C,D ;Togo et al 2004;White et al 2005).…”
Section: Histone H2a Ubiquitylation Correlates With Repressed Genes Dmentioning
confidence: 99%
“…These programs include hormone biosynthesis, lipid and amino acid metabolisms, and nucleotide biosynthesis. The transcription network revealed by microarray expression profiling during hepatocyte regeneration indicated that Igfbp1, LCN2, and Saa2 increase but, in contrast, Car3, Serpina6 (also called CBG; corticosteroid-binding globulin), and Cyp2f2 are manifestly decreased ∼12 h after hepatectomy (Togo et al 2004;White et al 2005). These genes are also important for hepatic regeneration, in terms of homeostasis and hepatic metabolism.…”
mentioning
confidence: 99%